2006
DOI: 10.1111/j.1463-1326.2006.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of underfeeding on whole‐body carbohydrate partitioning, thermogenesis and uncoupling protein 3 expression in human skeletal muscle

Abstract: Underfeeding for 6 days has no significant effect on UCP3 mRNA expression in skeletal muscle in non-obese men but is associated with changes in carbohydrate fuel partitioning, REE and the thermogenic response to the glucose clamp. Mild underfeeding had no effect on insulin sensitivity, but more severe energy restriction reduced insulin-stimulated glucose oxidation without affecting glucose storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…7,8,17 Similarly, further studies have demonstrated a decline in clamp-derived IS within 24 h (200 kcal per day) and 5 days (À50% energy) of CR, respectively. 10,11 Severe carbohydrate restriction induces postprandial hyperglycemia and IR at skeletal muscle to shift fuel to the brain. 41 As to the mechanisms, increased FFA availability through increased lipolysis (Table 2 and 3), together with endocrine alterations (e.g., elevated growth hormone levels) and stress-response 42 add to impair IS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,17 Similarly, further studies have demonstrated a decline in clamp-derived IS within 24 h (200 kcal per day) and 5 days (À50% energy) of CR, respectively. 10,11 Severe carbohydrate restriction induces postprandial hyperglycemia and IR at skeletal muscle to shift fuel to the brain. 41 As to the mechanisms, increased FFA availability through increased lipolysis (Table 2 and 3), together with endocrine alterations (e.g., elevated growth hormone levels) and stress-response 42 add to impair IS.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,17 Studies with less severe CR, however, provided rather inconsistent results. Although some studies have found an impairment of IS within 1 --5 days of CR (p50% energy) in healthy lean subjects, 10,11 clamp-derived IS has been shown to be sustained following 7 days of CR at an energy intake of 60 kJ kg À1 body weight per day. 9 By contrast, long-term CR has been shown to improve fasting and oral glucose tolerance test (OGTT)-derived indices of IS.…”
Section: Introductionmentioning
confidence: 99%
“…Even when animal models of dietary-induced obesity are considered, there is little or no stratification of obese animals in terms of phenotype or gene expression. A considerable amount of research effort is currently being put into the development of drugs to enhance fat metabolism in obese subjects -the central hypothesis is that obesity is associated with impaired fat metabolism (18,19). However, the findings from our study demonstrate that some obese individuals have a considerably higher fat oxidation capacity than lean individuals.…”
Section: Variability In Human Cells and Subjects: Goldmine Or Gordianmentioning
confidence: 53%
“…However, the effects of short-term caloric restriction are different. In one study, 11 subjects were fed for two periods of 6 days with hypo- and eucaloric diet with the same macronutrient composition in random order [34]. At 6 days, fasting FFAs significantly increased with the hypocaloric diet compared with the eucaloric diet [34].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 11 subjects were fed for two periods of 6 days with hypo- and eucaloric diet with the same macronutrient composition in random order [34]. At 6 days, fasting FFAs significantly increased with the hypocaloric diet compared with the eucaloric diet [34]. Whether the macronutrient composition affects FFAs was investigated in an animal model, and the study found that energy-restricted high-fat versus low-fat diet did not result in different FFA levels [35].…”
Section: Discussionmentioning
confidence: 99%